KONSOLIDASI POTENSI PEMBANGUNAN: STUDI TENTANG PENANGANAN KEMISKINAN DI KECAMATAN MUARA MUNTAI-KUTAI KARTANEGARA - Sonny Sudiar (Jurnal Paradigma (JP), 2017)
The implementation of development program is a reality must be conducted by the local government in Indonesia, including Kutai Kartanegara. Unfortunetly, implemented development not always produces social welfare as it does. It sometimes creates poverty and environment degradation. Poverty has becomes undeniable social problem. It was also happen in Kutai Kartanegara, poverty problem still need a serious attention by government. This article was intented to explain the cause factors of poverty in sub-district Muara Muntai Kutai Kartanegara, furthermore it investigates about the handling method. The results show that there  were three causes of poverty: structural factor, natural factor, and cultural factor. To handle poverty problem the government was implementing human empowerment strategy and consolidate the development potency.